Pengaruh Social Media Engagement Tiktok Terhadap Impulse Buying Produk Pakaian Pada Dewasa Awal - Vidi Vitara; Meike Kurniawati (Jurnal Humanipreneur, 2023)
Social media engagement (SME) is an individual's activity of viewing content, liking, sharing, and commenting which can increase individual involvement with content on social media. The high SME experienced by individuals can increase impulse buying (IB) decisions, purchase without thinking and based on pleasure with the product. This research uses a quantitative study to explain the effect of Tiktok's social media engagement on impulse buying of online clothing content in early adults. Participants obtained in this study were 131 early adult samples. The results of simple linear regression analysis can be seen that SME positively and significantly affects IB (F = 41.941, p = 0.000 <0.05) with a contribution of 24.8%.